Changing bodies, changing lives a book for teens on sex and relationships - Alexander, Ruth Bell (New York Random House, 1980)
Candidly discusses teenage sexuality and the many physical and emotional changes that occur during adolescence.
Includes bibliographies and index.
Keywords: Sex instruction for youth